Genetic diversity and population structure of elite maize (Zea mays) inbred lines using phenotypic data and single nucleotide polymorphisms - Elmyhun, Melkamu; Abate, Ermias; Abate, Alemu; Menkir, Abebe; Chere, Adefris Teklewold (Wiley, 2025)
Maize (Zea mays L.) is a staple food crop in Ethiopia, providing essential calories, minerals and vitamins to millions. Despite significant investments in developing high-yielding varieties and hybrids, maize yields remain suboptimal because of various production constraints. Understanding the genetic diversity of adapted maize inbred lines is crucial for optimizing heterosis in hybrids and enhancing resistance to biotic and abiotic stresses. The present study was designed to integrate 11 agronomic traits and 3155 SNP markers to assess the genetic diversity among 107 maize inbred lines. Significant differences among the lines were observed for all measured traits. Cluster analysis of agronomic traits identified three distinct groups, with Group III comprising high-yielding and late blight-resistant lines. Genetic diversity assessment using SNPs also identified three groups, with pairwise Euclidean genetic distances ranging from 2.4 to 3.4. Cluster analysis using both data types consistently identified three distinct groups, with the largest genetic distance occurring between Groups II and III. Principal component analysis identified days to anthesis, days to silking and late blight resistance as key traits contributing to the observed phenotypic variation among the lines. Joint analysis of phenotypic and molecular data revealed notable discrepancies in clustering patterns, with only 12% agreement between the two methods, suggesting that phenotypic and genotypic data capture different dimensions of genetic variation. These findings offer valuable insights for selecting parents in breeding programmes focused on enhancing disease resistance, yield stability and adaptability in maize.